The Complete Genome Sequence of Campylobacter jejuni Strain 81116 (NCTC11828) - Pearson, Bruce M. (American Society for Microbiology (ASM), 2007)

(untitled)
Campylobacter jejuni is a major human enteric pathogen that displays genetic variability via genomic reorganization and phase variation. This variability can adversely affect the outcomes and reproducibility of experiments. C. jejuni strain 81116 (NCTC11828) has been suggested to be a genetically stable strain (G. Manning, B. Duim, T. Wassenaar, J. A. Wagenaar, A. Ridley, and D. G. Newell, Appl. Environ. Microbiol. 67:1185-1189, 2001), is amenable to genetic manipulation, and is infective for chickens. Here we report the finished annotated genome sequence of C. jejuni strain 81116.